2012
DOI: 10.4103/0019-5154.103060
|View full text |Cite
|
Sign up to set email alerts
|

Origin Use of CD4, CD8, and CD1a Immunostains in Distinguishing Mycosis Fungoides from its Inflammatory Mimics: A Pilot Study

Abstract: Patch-stage/early mycosis fungoides (MF) is difficult to differentiate from benign dermatoses, despite several robust histologic criteria. Most studies include advanced lesions and data about early disease is limited.Objectives:(1) To compare the CD4:CD8 ratio in patch-stage MF versus inflammatory mimics. (2) To study patterns of CD1a expression in the epidermis and dermis in the two groups.Materials and Methods:Twenty cases each of early MF and inflammatory dermatoses were selected. The diagnoses were establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
2
5
0
2
Order By: Relevance
“…In the present study CD4:CD8 ratio in the D-E Junction of cases of LP was in a range of 0.42-0.48 which was in concordance with the study done by Rana S et al [12]. It was also correlating with the study done by Tirumalae R et al [13] who described the CD4:CD8 ratio of 0.9 in inflammatory disease. The CD4:CD8 ratio in the dermo-epidermal junction was also in comparison with Scott R. Florell et al [14] who described a ratio of 1 in benign conditions ( Table 3).…”
Section: Study Cd4:cd8 T Cell Ratio In the Papillary Dermis Of Normalsupporting
confidence: 93%
“…In the present study CD4:CD8 ratio in the D-E Junction of cases of LP was in a range of 0.42-0.48 which was in concordance with the study done by Rana S et al [12]. It was also correlating with the study done by Tirumalae R et al [13] who described the CD4:CD8 ratio of 0.9 in inflammatory disease. The CD4:CD8 ratio in the dermo-epidermal junction was also in comparison with Scott R. Florell et al [14] who described a ratio of 1 in benign conditions ( Table 3).…”
Section: Study Cd4:cd8 T Cell Ratio In the Papillary Dermis Of Normalsupporting
confidence: 93%
“…Several studies demonstrated that eosinophils also play a major role in the pathogenesis of allergic dermatitis 48. Apart from mast cells and eosinophils, other components of the skin immune system such as T cells play an important role in the course of allergic dermatitis 49,50. CD4 is expressed in T-helper cells and is found in approximately 80% of thymocytes and in 45% of peripheral blood lymphocytes 51,52.…”
Section: Discussionmentioning
confidence: 99%
“…Гистологические признаки стадий классического варианта ГМ Соотношение CD4/CD8-лимфоцитов Одним из важных критериев диагностики ГМ является определение соотношения лимфоцитов с маркерами cD4/cD8 в коже. установлено, что у пациентов с воспалительными заболеваниями этот показатель ниже, чем у больных с ранними стадиями ГМ [5,16].…”
Section: таблицаunclassified